Analysis of the Effect of Sales Growth, Inventory Turnover and Growth Opportunities on Profitability and Stock Return - Hasanudin (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This study aims to determine the effect of sales growth, inventory turnover, and growth opportunities on profitability and stock returns in manufacturing companies in the fast-moving consumer goods sub-sector. For the independent variables, sales growth (X1), inventory turnover (X2), and growth opportunities (X3). The dependent variable is the return on assets (Y1), return on equity (Y2), and stock returns (Y3). The analytical method used is descriptive analysis with Structural Equation Model (SEM) using the financial statements of six fast-moving consumer goods sub-sector manufacturing companies from 2014 – 2018. This study finds that Sales Growth has a positive but not significant effect on Return on Assets. Return on Equity and Stock Return of the company. Inventory Turnover has a positive impact on Return on Assets and Return on Equity of the company, while Inventory Turnover does not affect Stock Return. And Growth Opportunities have a negative influence on Return on Assets, Return on Equity, and Stock Returns.